Pengembangan Algoritma A-Star dengan Penyesuaian Heuristik untuk Pencarian Rute Optimal - Sukroni, Achmad Faiz; Juhari, Juhari; Nasichuddin, Achmad (Jurnal Riset Mahasiswa Matematika, 2024)
The The A-Star algorithm is one of the most popular shortest route search algorithms due to its effectiveness in finding optimal solutions. This study focuses on modifying the A-Star algorithm to improve its performance in optimizing the shortest route. The study was conducted by comparing the standard A-Star algorithm and its modified version based on the number of iterations required to reach the optimal solution. The assessment was carried out manually and through a computer program using sample data from tourist locations in Blitar as a case study. The results of the analysis in 20 comparative experiments showed that the modified A-Star algorithm was able to minimize the number of iterations by up to 32% compared to the standard A-Star algorithm. This finding indicates that the modifications made to the A-Star algorithm can increase efficiency without reducing the accuracy of the results. This study provides an important contribution to the development of shortest route search algorithms, especially in their application to the tourism sector and navigation systems.